2020
DOI: 10.1002/jeab.595
|View full text |Cite
|
Sign up to set email alerts
|

The Δ–∑ hypothesis: How contrast and reinforcement rate combine to generate suboptimal choice

Abstract: When given a choice between two alternatives, each offering food after the same delay with different but signaled probabilities, pigeons often prefer the low probability alternative. This preference is surprising because pigeons fail to maximize the rate of food intake; they exhibit a suboptimal preference. We advance a new explanation, the Δ-P hypothesis, in which the difference in probability of reinforcement within terminal links (Δ) and the overall reinforcement probability rate of each alternative ( P ) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 29 publications
6
50
0
Order By: Relevance
“…To test this prediction, we pitted a Δ = .5 option, constructed with different pairs of probability values, against a Δ = 0 option, constructed with the same probability of .5 in both terminal links. In Experiment 1, we replicated the results from previous research (González et al, 2020), finding a preference for Δ = .5 relative to Δ = 0 when the former was constructed with the pair .75/.25. A preference for Δ = .5 was also obtained with the new pair 1/.5.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…To test this prediction, we pitted a Δ = .5 option, constructed with different pairs of probability values, against a Δ = 0 option, constructed with the same probability of .5 in both terminal links. In Experiment 1, we replicated the results from previous research (González et al, 2020), finding a preference for Δ = .5 relative to Δ = 0 when the former was constructed with the pair .75/.25. A preference for Δ = .5 was also obtained with the new pair 1/.5.…”
Section: Discussionsupporting
confidence: 81%
“…Results from two experiments showed that animals were sensitive to both higher-order variables (González et al, 2020). In Experiment 1, the Δs varied across conditions while the Σs remained equal.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The newly proposed Delta-Sigma hypothesis (González et al 2020), on the other hand, suggests that the contrast, defined as the difference between the two reinforcement probabilities associated with each terminal link within an alternative (Delta, ∆), and the overall reinforcement probability of each alternative (Sigma, ∑) are the main determinants of choice. In the standard task (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the temporal dynamics of value accumulation by two stimuli (S 1 ± , and S 2 ± ) presented sequentially may be lessened compared to the single-stimulus situation (S ± ). On the other hand, the ∆-∑ hypothesis (González et al 2020) was conceived for the two-option variation and assumed that the single-option version was equivalent under certain conditions. Applying the ∆-∑ hypothesis to the optimal alternative in the original procedure is not straightforward because, with only one terminal link stimulus, we cannot compute ∆.…”
Section: Introductionmentioning
confidence: 99%